Pengolahan Lidah Buaya (Aloe Vera) Menjadi Granul Effervescent sebagai Minuman Kesehatan dan Analisis Peningkatan Nilai Ekonomisnya - Ramadhia, Muflihah; Ichsan, Ichsan (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
One of the leading sectors of commodities mainstay of West Kalimantan which have a comparative advantage, especially in the city and district of North Pontianak is aloe vera. Aloe vera usually processed and sale only in the form of raw material and provide little added economic value to society. The purpose of this study is knowing and producing effervescent granules with the best formulations as a health drink; and knowing and determining the economic value and feasibility level production of effervescent granules as a busniess unit. The result of this study indicate that, based on the soluble time test aloe vera effervescent granules are not eligible. Effervescent granules solubility test is qualified. Water content test of aloe vera effervescent granules is qualified. Flow time test of aloe vera effervescent granules is qualified. Meanwhile, based on the analysis of the calcualtion of the increase in economic value by using the calculation of Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), Payback Period (PP) and the Discounted Payback (DPB) expresses feasible to increase the economic value of public income.